Customs Broker Services Operational Performance: Basis for the Development of Corporate Strategy - Sernero, Reymer (Journal of Interdisciplinary Perspectives, 2024)
This study investigated the operational performance of customs brokers and its implications for developing a corporate strategy. In total, 277 respondents participated, comprising 121 customs brokers and 156 importers from the Philippines, providing demographic information and responding to self-administered questionnaires. We evaluated operational performance based on quality, speed, dependability, flexibility, and cost using a 4-point Likert scale. The findings revealed that both groups of respondents highly rated customs brokers in terms of quality, dependability, flexibility, and cost. Specific examples illustrating these high ratings were noted. We analyzed differences based on demographic profiles between customs brokers and importers, including gender, speed, and educational attainment. Significant differences were found based on gender and speed. Additionally, variations in educational attainment were identified regarding dependability and flexibility. A significant difference was observed between customs brokers and importers regarding operational performance objectives in terms of speed, with customs brokers rated higher than importers. Addressing this identified difference by implementing targeted measures to enhance speed can contribute to overall operational improvement, meeting the time-sensitive needs of importers and further strengthening the reputation of customs brokers. These findings have practical implications for developing a strategy to enhance the operational performance of customs broker services. By recognizing their strong performance in quality, dependability, flexibility, and cost, customs brokers can continue to prioritize and maintain high standards in these areas, thereby improving overall service delivery.